Does the BCG vaccine have different effects on strains of tuberculosis?. (1st December 2020) - Kousha, A.; Farajnia, S.; Ansarin, K.; Khalili, M.; Shariat, M.; Sahebi, L.
Summary: Several explanations have been suggested concerning the variety in bacille Calmette–Guerin (BCG) vaccine efficacy on strains of Mycobacterium tuberculosis ( Mtb ). This study aimed to compare the effect of BCG vaccination history in the prevention of the occurrence of Mtb ‐Beijing and non‐Beijing strains. In this cross‐sectional study, 64 patients with pulmonary tuberculosis (TB) were recruited from the Iranian border provinces (North West and West). Isolates were subjected to restriction fragment length polymorphism (RFLP) analysis, using the insertion sequence IS6110 as a probe ( IS6110 RFLP) and drug susceptibility testing using the proportion method. Samples were analyzed with Gel Compare II 6.6 and spss version 18. The mean age [standard deviation (SD)] of the patients was 54·4 (SD = 17·0). Overall, 49 cases (76·56%) had no BCG vaccination scar. The prevalence of Beijing strains was 9·38% and drug resistance proportion among the isolates was 14·1% (nine cases). There was a significant relationship between Beijing strains and tuberculosis (TB)‐drug resistance in isolates (χ 2  = 26·29, P  < 0·001). There was also a strong association between vaccination history and Beijing strains (χ 2  = 13·23, P  = 0·002). Also, a statistical relationship was observed between Beijing strains and drug‐resistant TB among patients with a history of vaccination (χ 2  = 7·47, P  = 0·002). This association was not maintained in the unvaccinated group ( P  = 0·102). These findings confirm the claim that the vaccine has different effects on different subspecies of tuberculosis. The cause of the high probability of drug resistance in patients with Beijing‐TB and vaccination history requires further investigation with a higher sample size. Abstract : Detection of the effectiveness of the BCG vaccine in the prevention of tuberculosis in different subspecies and treatment‐resistant tuberculosis is critical and could be a major step in improving the vaccine. Our findings approve the claim that the BCG vaccine has different protective effects on Beijing strains of tuberculosis